The risk of postoperative complications following preoperative immunosuppressive therapy in patients undergoing ileocolonic resection for Crohn's disease - Yamamoto, T. (2014)
Yokkaichi Social Insurance Hosp, Ctr Inflammatory Bowel Dis, Yokaichi, Japan